Two new species of Pharta Thorell, 1891 with the description of Ibana senagang gen. et sp. nov. (Araneae: Thomisidae) - Benjamin, Suresh P. (Zootaxa, 2014)
Two new species of Pharta, P. sudmannorum sp. nov. (♂♀, Borneo) and P. koponeni sp. nov. (♂, Thailand) are described. Furthermore, Ibana senagang gen. nov. & sp. nov. from Malaysia is described based on its exceptional palp, which has a reduced, movable conductor and thick-long spines on the distal, ventral surface of the tibia, reminiscent of Epidius Thorell, 1877.